Prenatal exposure to antidepressants and language competence at age three: results from a large population‐based pregnancy cohort in Norway. (14th April 2014) - Skurtveit, S; Selmer, R; Roth, C; Hernandez‐Diaz, S; Handal, M
<x xml:space="preserve">Abstract</x> Objective To examine the association between maternal use of selective serotonin reuptake inhibitors (SSRI) in pregnancy and language competence in their children at age three taking into account maternal symptoms of anxiety and depression. Design Population‐based prospective pregnancy cohort study. Setting The Norwegian Mother and Child Cohort Study; recruited pregnant women from 1999 through 2008. Population 45 266 women with 51 748 singleton pregnancies. Methods The association between short‐ or long‐term use of SSRI during pregnancy and language competence in the child was investigated using multinomial logistic regression with three outcome categories: long, complicated sentences, fairly complete sentences and language delay. Main outcome measures Children's language competence at age three measured by maternal report on a validated language grammar scale. Results Women reported use of SSRI in 386 (0.7%) pregnancies. Of these, 161 (42%) reported long‐term use. Compared with children whose mothers took no SSRI, using the best language category as the reference, adjusted relative risk ratios (RRR) of having fairly complete sentences were 1.21 (95% CI 0.85–1.72) and 2.28 (1.54–3.38) for short‐ and long‐term SSRI use, respectively. The adjusted RRRs of language delay were 0.86 (0.42–1.76) and 2.30 (1.21–4.37). Symptoms of anxiety and depression in pregnancy were independently related to language delay, adjusted RRR 1.25 (1.03–1.50) and 1.83 (1.40–2.40) for short‐ and long‐term symptoms, respectively. Conclusions Prolonged use of SSRI during pregnancy was associated with lower language competence in children by age three independently of depression. Having symptoms of depression throughout pregnancy had an independent effect.